Development of biological process with pure bacterial cultures for effective bioconversion of sewage treatment plant sludge - Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Jamal, Parveen (Taylor & Francis, 2007)
Forty-six bacterial strains were isolated from nine different sources in four treatment plants namely IndahWater Konsortium (IWK)sewage treatment plant (STP), International Islamic University Malaysia (IIUM) wastewater treatment plant-1,-2 and -3 to evaluate the bioconversion process in terms of efficient biodegradation and bioseparation. The bacterial strains isolated were found to be 52.2% (24 isolates) and 47.8% (22 isolates) in the IWK and IIUM treatment plants, respectively. The results showed that higher microbial population (9–10 × 104 cfu/mL) was observed in the secondary clarifier of IWK treatment plant. Among the isolates, 23 isolates were gram-positive bacillus (GPB) and gram-positive cocci (GPC), 19 isolates were gram-negative bacillus (GNB) and gram-negative cocci (GNC), and the rest were undetermined. Gram-negative cocci (GNC) were not found in the isolates from IWK. A total of 15 bacterial strains were selected for effective and efficient sludge bioconversion. All the strains were tested against sludge (1% total suspended solids, TSS) to evaluate the biosolids production (TSS% content), chemical oxygen demand (COD) removal and filtration rate (filterability test). The strain S-1 (IWK1001) showed lower TSS content (0.8% TSS), maximumCODremoval (84%) and increased filterability (1.1 min/10 mL of filtrate) of treated sludge followed by the strains S-11, S-14, S-2, S-15, S-13, S-7, S-8, S-4, S-3, S-6, S-12,S-16, S-17 and S-9. The pH values in the fermentation broth were affected by the bacterial cultures and recorded as well. Effective bioconversion was observed during the first three days of sludge treatment.